Impact of age and comorbidity on treatment of non-small cell lung cancer recurrence following complete resection: A nationally representative cohort study. (December 2016) - Wong, Melisa L.; McMurry, Timothy L.; Stukenborg, George J.; Francescatti, Amanda B.; Amato-Martz, Carla; Schumacher, Jessica R.; Chang, George J.; Greenberg, Caprice C.; Winchester, David P.; McKellar, Daniel P.; Walter, Louise C.; Kozower, Benjamin D.
Highlights: 33.8% of stage I–III NSCLC patients developed postoperative recurrence at 5 years. 79.5% of patients with locoregional recurrence received active cancer treatment. 77.3% of patients with distant recurrence received active cancer treatment. Older patients, independent of comorbidity, were less likely to receive treatment. Women and those with substance abuse were also less likely to receive treatment. Abstract: Objective: Older patients with non-small cell lung cancer (NSCLC) are less likely to receive guideline-recommended treatment at diagnosis, independent of comorbidity. However, national data on treatment of postoperative recurrence are limited. We evaluated the associations between age, comorbidity, and other patient factors and treatment of postoperative NSCLC recurrence in a national cohort. Materials and methods: We randomly selected 9001 patients with surgically resected stage I–III NSCLC in 2006–2007 from the National Cancer Data Base. Patients were followed for 5 years or until first NSCLC recurrence, new primary cancer, or death, whichever came first. Perioperative comorbidities, first recurrence, treatment of recurrence, and survival were abstracted from medical records and merged with existing registry data. Factors associated with active treatment (chemotherapy, radiation, and/or surgery) versus supportive care only were analyzed using multivariable logistic regression. Results: Median age at initial diagnosis was 67; 69.7% had >1 comorbidity. At 5-year follow-up, 12.3% developed locoregional and 21.5% developed distant recurrence. Among patients with locoregional recurrence, 79.5% received active treatment. Older patients (OR 0.49 for age >75 compared with <55; 95% CI 0.27–0.88) and those with substance abuse (OR 0.43; 95% CI 0.23–0.81) were less likely to receive active treatment. Women (OR 0.62; 95% CI 0.43–0.89) and patients with symptomatic recurrence (OR 0.69; 95% CI 0.47–0.99) were also less likely to receive active treatment. Among those with distant recurrence, 77.3% received active treatment. Older patients (OR 0.42 for age >75 compared with <55; 95% CI 0.26–0.68) and those with any documented comorbidities (OR 0.59; 95% CI 0.38–0.89) were less likely to receive active treatment. Conclusion: Older patients independent of comorbidity, patients with substance abuse, and women were less likely to receive active treatment for postoperative NSCLC recurrence. Studies to further characterize these disparities in treatment of NSCLC recurrence are needed to identify barriers to treatment.